Rice OseIF6.1 encodes a eukaryotic translation initiation factor and is essential for the development of grain and anther - Guo, Hongming; Lv, Jianqun; Su, Xiangwen; Chen, Liang; Ren, Juansheng; Liu, Liping; Ren, Mingxin; Liu, Song; Dai, Mingli; Ren, Guangjun; Gao, Fangyuan (Frontiers in Plant Science, 2024)
The eIF6 proteins are distributed extensively in eukaryotes and play diverse and essential roles. The bona fide eIF6 protein in Arabidopsis, At-eIF6;1, is essential for embryogenesis. However, the role of eIF6 proteins in rice growth and development remains elusive and requires further investigation. Here, we characterized the functions of OseIF6.1, which is homologous to At-eIF6;1. OseIF6.1 encodes an eukaryotic translation initiation factor with a conserved eIF6 domain. The knockdown of OseIF6.1 resulted in a decrease in grain length and pollen sterility, whereas the overexpression of OseIF6.1 displayed opposite phenotypes. Further studies revealed that OseIF6.1 regulates grain shape by influencing cell expansion and proliferation. In addition, OseIF6.1 interacts with OsNMD3, which is a nuclear export adaptor for the 60S ribosomal subunit. The knockdown of OsNMD3 in plants exhibited reduced fertility and seed setting. Therefore, our findings have significantly enriched the current understanding of the role of OseIF6.1 in rice growth and development.